PERAN HUKUM KETERBUKAAN INFORMASI SEBAGAI KATALISATOR OPTIMALISASI PERAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Basri, Alamsyah Alam (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
This article analyzes the role of the Corruption Eradication Commission (KPK) in the context of combating corruption in Indonesia, focusing on the challenges of institutional weakening and performance stagnation it faces. The widespread and systematic nature of corruption indicates underlying structural issues within state administration, rather than merely reflecting societal culture. Since the reform era, the KPK was established as an independent institution with broad authority in investigation, prosecution, and coordination, as well as supervision over other law enforcement agencies. However, the decline in Indonesia's Corruption Perception Index (CPI) in 2022 and the stagnation in case handling by law enforcement, including the KPK, raise questions about its effectiveness. This research employs a normative legal research method with a statute approach and a case approach. The analysis indicates that the KPK remains crucial for corruption eradication, despite facing issues of regulatory weakening (Law No. 19 of 2019) and internal challenges such as dual loyalty among seconded staff and ambiguities in the Supervisory Board's duties. Optimizing the KPK's performance requires strong political commitment from the government, strengthened coordination and supervision among law enforcement agencies, and ensuring the principles of integrity and public information disclosure in every stage of case handling.